Perancangan Break-time Space untuk Siswa dan Siswi SDK Santo Carolus Surabaya - Grace Gondosaputro (Intra, 2017)
Social gap has been a social phenomenon which is inseparable from people’s life, including in Saint Carolus Elementary School Surabaya. The gap among the grades has been growing into a habit where the juniors feel afraid to seniors. This affects the juniors couldn’t interact in the best way. Thus, a solution to minimize social gap impact is needed more than to eliminate the gap from people’s life, because finding the solution eliminating the gap that has been rooted would be too hard to do. This design is done with Design Thinking method, as it was popularize by Tim Brown, the CEO of IDEO. This method has 3 main steps which are inspiration, ideation and implementation. A design called Break-time Space is produced through the process. It is an area for break time can be used for interacting, playing and eating. It is hoped that this design will minimize the impact of social gap to make a better students’ interactions among partners and environments.